2014
DOI: 10.1111/tpj.12483
|View full text |Cite
|
Sign up to set email alerts
|

Rice germline‐specific Argonaute MEL1 protein binds to phasiRNAs generated from more than 700 lincRNAs

Abstract: SUMMARYSmall RNAs that interact with Argonaute (AGO) proteins play central roles in RNA-mediated silencing. MEI-OSIS ARRESTED AT LEPTOTENE1 (MEL1), a rice AGO, has specific functions in the development of pre-meiotic germ cells and the progression of meiosis. Here, we show that MEL1, which is located mostly in the cytoplasm of germ cells, associates preferentially with 21-nucleotide phased small interfering RNAs (phasiRNAs) that bear a 5 0 -terminal cytosine. Most phasiRNAs are derived from 1171 intergenic clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
264
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(276 citation statements)
references
References 51 publications
12
264
0
Order By: Relevance
“…Recently it has been shown that the rice Argonaute MEL1 (13) binds 21-nt phasiRNAs (14). The closest homolog of MEL1 in maize is AGO5c (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it has been shown that the rice Argonaute MEL1 (13) binds 21-nt phasiRNAs (14). The closest homolog of MEL1 in maize is AGO5c (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…MEL1, a rice homolog of Arabidopsis AGO5, mainly localizes to the cytoplasm of premeiotic cells (13). Recently MEL1 was shown to selectively bind 21-nt phasiRNAs (14). mel1 loss of function mutants have abnormal tapetum and aberrant pollen mother cells (PMCs, the final differentiated state before the start of meiosis) that arrest in early meiosis (13), suggesting that 21-nt phasiRNAs are crucial for male fertility.…”
Section: Significancementioning
confidence: 99%
“…Like AGO5 in Arabidopsis, MEL1/ AGO5c predominantly associated with 21-nucleotide phased siRNAs (phasiRNAs) that are mainly derived from intergenic regions and initiate with a 59 C (Komiya et al, 2014). The function of MEL1/phasiRNA complexes remains obscure, yet the cytoplasmic localization of MEL1 implies a potential role of MEL1/phasiRNA in posttranscriptional regulation of genes.…”
Section: Ago1/5/10 Cladementioning
confidence: 99%
“…Arabidopsis AGO7 (also known as ZIP) specifically binds miR390 (Montgomery et al, 2008), which targets TAS3 transcripts (Bohmert et al, 1998;Morel et al, 2002;Vaucheret et al, 2004;Baumberger and Baulcombe, 2005;Qi et al, 2005;Zhang et al, 2006) ta-siRNAs vsiRNAs OsAGO1a Os02g45070 miRNAs Plant development, antiviral defense Os04g47870 miRNAs Plant development, antiviral defense (Wu et al, , 2015 (Takeda et al, 2008;Tucker et al, 2012;Brosseau and Moffett, 2015) vsiRNAs OsAGO5c Os03g58600 phasiRNAs Germ cell division (Nonomura et al, 2007;Komiya et al, 2014) AtAGO10 AT5G43810 miR165/166 SAM development, antiviral defense (Moussian et al, 1998;Lynn et al, 1999;Liu et al, 2009;Ji et al, 2011;Zhu et al, 2011;Garcia-Ruiz et al, 2015;Zhou et al, 2015) miR172 vsiRNAs (Harvey et al, 2011;Jaubert et al, 2011;Wang et al, 2011b;Zhang et al, 2011;Wei et al, 2012) vsiRNAs miR393* AtAGO3 AT1G31290 n.d. n.d. AtAGO7 AT1G69440 miR390 ta-siRNA biogenesis, phase transition, antiviral defense (Hunter et al, 2003;Adenot et al, 2006;Montgomery et al, 2008;Qu et al, 2008) OsAGO7 Os03g33650 miR390 ta-siRNA biogenesis, SAM development (Nagasaki et al, 2007) ZmAGO7 GRMZM5G892991 miR390 ta-siRNA biogenesis, leaf development (Douglas et al, 2010) AtAGO4 AT2G27040 hc-siRNAs DNA methylation, antibacterial immunity, defense against DNA viruses (Zilberman et al, 2003;Li et al, 2006;Pontes et al, 2006;…”
Section: Ago2/3/7 Cladementioning
confidence: 99%
“…Later, the phenomenon known as co-suppression in plants and quelling in fungi, in which transgenes suppress the accumulation of endogenous transcripts based on the homology between transgenes and endogenous transcripts (Romano and Macino 1992;Napoli et al 1990 (Sawano et al 2017). In addition, Komiya (2017) reviewed the phased small interfering RNAs (phasiRNAs) recently identified in plants, small RNAs that are generated from a long RNA precursor at intervals of 21-26-nt (Komiya et al 2014). phasiRNAs are also loaded on AGO proteins, and the phasiRNA biogenesis was initiated by miRNA-dependent cleavage of precursor in plants.…”
mentioning
confidence: 99%